A basic structure of human existence and the dying process. - Walford, Virginia Lynn. (University of Ottawa (Canada), 1991)
This thesis suggests a metatheoretical frame of reference for the dying process, a perspective that differs considerably from the stage theories postulated by other authors. These stage theories and other approaches are highlighted and their shortcomings and limitations reviewed and discussed. This thesis proposes that the concept of temporality can overcome the identified shortcomings and provide a more comprehensive framework for clinical intervention. Temporality refers to an integration of past, present and future in a person's existence. The dynamic interchange among these modes of time has profound implications in a person's experiencing of life and death. This thesis takes the traditional notions of denial and acceptance and redefines them using the concept of temporality. Using this basic structure to understand the dying process enables an understanding of how meaning is created. Implications for the management of the temporal structure of experience are discussed along with clinical examples. Future directions for incorporating this framework are proposed.
Keywords: Psychology, General.